2022
DOI: 10.3390/traumacare2020026
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Contribution Accumulation Makes to Psychological and Physical Trauma Sustained through Childhood Maltreatment

Abstract: The pervasive effects of cumulative harm resulting from adverse childhood experiences influence all aspects of an individual’s life course. Research highlights a relationship between accumulation and trauma symptomology across all domains of harm and risk. A systematic literature review was conducted to explore and synthesize the current evidence base for the contribution accumulation makes to psychological and physical injury of childhood trauma. A search was conducted relevant to two areas of interest: (a) “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Despite advancements in medical research and psychology, the precise mechanisms underlying conversion disorder remain elusive (9). However, a growing body of evidence suggests a strong correlation between adverse childhood experiences-such as physical, sexual, and emotional abuse, along with neglect-and the emergence of the disorder (10,11). It is proposed that such traumas may disrupt the development of effective coping mechanisms, leading to the conversion of emotional distress into physical manifestations (12).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancements in medical research and psychology, the precise mechanisms underlying conversion disorder remain elusive (9). However, a growing body of evidence suggests a strong correlation between adverse childhood experiences-such as physical, sexual, and emotional abuse, along with neglect-and the emergence of the disorder (10,11). It is proposed that such traumas may disrupt the development of effective coping mechanisms, leading to the conversion of emotional distress into physical manifestations (12).…”
Section: Introductionmentioning
confidence: 99%
“…ACEs have been consistently related to a greater risk of internalizing problems (e.g., depression or anxiety; Chapman et al, 2004 ) and externalizing problems (e.g., violence or delinquency; Ford et al, 2012 ) as a consequence of the traumatic damage suffered. Moreover, the risk of these problems seems to be even greater in those cases in which multiple types of ACEs occur simultaneously ( Finkelhor et al, 2007 , 2013 ; Bryce and Collier, 2022 ), in other words, when there is cumulative childhood adversity. In the field of CPV, numerous studies have found that both direct and witnessing parental abuse are powerful predictors of CPV (e.g., Calvete et al, 2014 ; Margolin and Baucom, 2014 ; Contreras and Cano-Lozano, 2016 ; Beckmann, 2019 ; Contreras et al, 2020 ; Ibabe et al, 2020 ; Simmons et al, 2020 ; Cano-Lozano et al, 2021b ; Navas-Martínez and Cano-Lozano, 2022a ), increasing the probability of CPV up to 70% (see Gallego et al, 2019 , for review).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the aforementioned, the literature suggests that childhood adversity has a series of negative effects on children’s developmental evolution. For example, it has been found that ACEs are related to insecure parental attachment and lower levels of resilience and emotional intelligence ( Arslan, 2016 ; Lätsch et al, 2017 ; Huang and Mossige, 2018 ; Barnett and Howe, 2021 ) and predicts insecure parental attachment style as well as emotional, adaptive, and behavioral problems in the child (see Bryce and Collier, 2022 , for review). These studies have also found correlations between attachment, resilience, and emotional intelligence, which are variables that could be included in attachment theory ( Bowlby, 1979 ).…”
Section: Introductionmentioning
confidence: 99%
“…and externalizing variables (aggressiveness, inattention, criminal behavior, etc.) ( Bryce & Collier, 2022 ; MacKenzie et al, 2011 ). Holistic approaches also evaluate the consequences of such victimization for quality of life (QoL), defined by the World Health Organization (WHO) as a person’s perception of their objectives, expectations, standards, and concerns mediated by their cultural context and value system ( Saxena & Orley, 1997 ).…”
Section: Introductionmentioning
confidence: 99%